Energy Drinks – a Real Danger or a Scapegoat? An Analysis of the Commercially Available Products in Romania - Candel, Octav Sorin; Jitaru, Mihaela (Technium Social Sciences Journal, 2020)
Energy drinks are beverages that contain caffeine, taurine, ginseng, guarana, vitamins, herbal supplements, and sugar. Their ingredients are generally regarded as safe for consumption, but some of them raise some concerns. Caffeine is especially regarded as problematic, especially for some categories of consumers. Nevertheless, energy drinks also offer some advantages. In this study, we aimed to analyze the ingredients found in the energy drinks that were commercially available on the Romanian market. We analyzed products gathered over one year (March 2018 – March 2019). We used the information found on the companies’ websites and directly on the products. We included 120 energy drinks found on the market. Most of the inspected products (93.4 %) contained caffeine and/or taurine (75 %). Many other products contained herbal ingredients such as guarana and ginseng. Vitamins and minerals were also abundant in these products. The vitamin concentrations are mostly negligible. Finally, all the energy drinks contained preservatives, food colorants or stabilizers, ingredients that are safe and authorized for use. In conclusion, energy drinks’ consumption is mostly safe and all their ingredients are approved. However, special attention should be dedicated to some particular classes of consumers. Energy drinks should not be used in large quantities and children should be discouraged to consume them. The population must be further informed in regards to their risk, the negative effects when consumed in combination with alcohol and the danger they represent for children.